1991
DOI: 10.1111/j.1600-0447.1991.tb05573.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune system‐associated antigens on the surface of peripheral blood lymphocytes in patients with Alzheimer's disease

Abstract: We investigated the immune-associated antigens of peripheral lymphocytes from 13 patients with Alzheimer's disease (AD) and 13 age-matched healthy control subjects using two-color analysis with flow cytometry. Four ratios of immune-related antigens, T/B lymphocytes, CD4/CD8, CD4/CD45R and CD4/HLA-DR, were compared for the AD and control groups. The T/B and CD4/CD8 ratios did not differ between the groups, the ratio of CD4+CD45R+ subset in the AD group was lower than the ratio in the control group, and the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…Moreover, although MCI subjects had a slightly lower proportion of CD4+ cells, we saw no differences in the percentage of CD8+ cells and the ratio of CD4+/CD8+ cells between MCI and controls. These results are in agreement with other investigators who have found no differences in the distribution of CD4+ and CD8+ cells and CD4+/CD8+ ratios in AD patients compared to controls (Richartz-Salzburger et al, 2006;Ikeda et al, 1991).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, although MCI subjects had a slightly lower proportion of CD4+ cells, we saw no differences in the percentage of CD8+ cells and the ratio of CD4+/CD8+ cells between MCI and controls. These results are in agreement with other investigators who have found no differences in the distribution of CD4+ and CD8+ cells and CD4+/CD8+ ratios in AD patients compared to controls (Richartz-Salzburger et al, 2006;Ikeda et al, 1991).…”
Section: Discussionsupporting
confidence: 94%
“…A decrease in proliferation in peripheral blood mononuclear cells (PBMCs) of AD patients has also been found (Lombardi et al, 1999). However, other reports indicate no differences in either CD4/CD8 ratios (Ikeda et al, 1991), total lymphocytes (Dysken et al, 1992) or the percentage of CD3+ lymphocytes (total T lymphocytes) (Lombardi et al,. 1999) between AD and controls.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, although some immunologi cal components have been associated with the neuropathological alterations of AD [1][2][3][4][5][6][7][8], a conclusive in volvement of immunity in the pathogenesis of the disease is still under debate [34], Immune reactions in the periph eral blood may be expected to occur in brain regions of AD patients and particularly IL-2 and the appearance of IL-2 receptor may induce activation of a cascade reaction of immunity determining T cell and NK cell proliferation in the brain of subjects suffering from AD [5,35]. More over, activated lymphocytes can penetrate the bloodbrain barrier so inducing possible neuroimmunological changes in the brain parenchyma [6,36].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it has been shown that peripheral T lymphocytes isolated from AD patients demonstrate decreased amounts of the CD45R isoform compared with age-matched nondemented control subjects (Ikeda et al, 1991). To examine whether increasing CD45 activity could block microglial activation resulting from co-treatment with phen and A␤, we activated wild-type microglia with phen and A␤, added CD45 recombinant protein (20 U/ml) to these cells, and measured NO and TNF-␣ release.…”
Section: Discussionmentioning
confidence: 99%